2023
DOI: 10.3390/antiox12030697
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Study of Antioxidant Potential of Urolithins

Abstract: In this work, quantum chemical calculations based on density functional theory (DFT) were performed to predict the antioxidant potential of four bioactive gut microbiota metabolites of the natural polyphenols ellagitannins (ETs) and ellagic acid (EA), also known as urolithins (UROs). In order to evaluate their ability to counter the effect of oxidative stress caused by reactive oxygen species (ROS), such as the hydroperoxyl radical (•OOH), different reaction mechanisms were investigated, considering water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Different grades (1 mg/mL, 2 mg/mL, and 5 mg/mL) of both LER and LER-AgNPs were prepared by mixing the respective mass per milliliter of dH 2 O with 0.1 mM DPPH, incubated in dark, and absorbency at 517 nm was measured at the first, second, and third hours of incubation. The untreated 0.1 mM DPPH was run as control while ascorbic acid (100 µg/mL) was taken as a standard antioxidant drug via the standard procedure, as described by [45][46][47]. The % antioxidant potential was determined: % Antioxidant potential = Absorbance of control(nm) − Absorbance of test (nm) Absorbance of control(nm) (2)…”
Section: Dynamic Light Scattering Spectroscopy and Zeta Potentialmentioning
confidence: 99%
“…Different grades (1 mg/mL, 2 mg/mL, and 5 mg/mL) of both LER and LER-AgNPs were prepared by mixing the respective mass per milliliter of dH 2 O with 0.1 mM DPPH, incubated in dark, and absorbency at 517 nm was measured at the first, second, and third hours of incubation. The untreated 0.1 mM DPPH was run as control while ascorbic acid (100 µg/mL) was taken as a standard antioxidant drug via the standard procedure, as described by [45][46][47]. The % antioxidant potential was determined: % Antioxidant potential = Absorbance of control(nm) − Absorbance of test (nm) Absorbance of control(nm) (2)…”
Section: Dynamic Light Scattering Spectroscopy and Zeta Potentialmentioning
confidence: 99%
“…From a fundamental perspective, it is well established that various mechanisms associated with the antioxidant potential of polyphenols (such as hydrogen atom transfer (HAT), single electron transfer (SET), and other less common paths) can be explored through the use of electronic structure computations 6,7 and, thus, numerous computationally-based investigations on probing antioxidant-related mechanisms can be found in the recent literature. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Perhaps the main mechanism regarding antioxidant activity in polyphenols, the HAT mechanism, [23][24][25][26][27] can be written as ArOH + R -ArO + RH, (1) where an O-H bond is homolyticaly cleaved and an H atom is transferred from the polyphenol (ArOH) to the free radical (R ) to offset it (RH). Hence, bond dissociation enthalpies (BDEs) can be used to estimate the energy necessary for the O-H bonds to be broken.…”
Section: Introductionmentioning
confidence: 99%
“…Urolithin A (URO A), also known as 3,8-dihydroxy-urolithin, is a kind of microflora human metabolite that is formed by the gut microbiota from ellagitannins and ellagic acid [ 12 ]. It has been found to have a high potential for scavenging free radicals [ 13 ]. Numerous in vivo studies have shown that URO A has a wide range of pharmacological properties, including antioxidant, anti-inflammatory, and antiapoptotic effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%